2005
DOI: 10.1002/gepi.20071
|View full text |Cite
|
Sign up to set email alerts
|

Premature death of adult adoptees: Analyses of a case‐cohort sample

Abstract: Genetic and environmental influence on risk of premature death in adulthood was investigated by estimating the associations in total and cause-specific mortality of adult Danish adoptees and their biological and adoptive parents. Among all 14,425 non-familial adoptions formally granted in Denmark during the period 1924 through 1947, we selected the study population according to a case-cohort sampling design. As the case-control design, the case-cohort design has the advantage of economic data collection and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…The only large adoption study that has been published shows a correlation between Danish adoptees and their biological parents, especially for death that is due to vascular causes 30 . However, a later extension of this study found smaller effects 31 , and twin data 29 indicate that the overall genetic effect on premature death is minimal.…”
Section: Genetic Epidemiology Of Human Lifespanmentioning
confidence: 49%
“…The only large adoption study that has been published shows a correlation between Danish adoptees and their biological parents, especially for death that is due to vascular causes 30 . However, a later extension of this study found smaller effects 31 , and twin data 29 indicate that the overall genetic effect on premature death is minimal.…”
Section: Genetic Epidemiology Of Human Lifespanmentioning
confidence: 49%
“…In the studies of parent-offspring pairs, genetic effects on mortality with infections were found in the earliest birth cohorts of adoptees [20][22]. In a study of adoptees and their siblings, belonging to a sample that is part of this study, evidence for a genetic effect on mortality from infection was seen in all birth cohorts [23].…”
Section: Discussionmentioning
confidence: 76%
“…From the Adoption Register, we also selected a sub-cohort consisting of a random sample of 1,933 adoptees, originally designed as an equally sized control sample in a study of the general mortality in this cohort [16]. We excluded the 30 suicides and used the others to represent adoptees who had not died by suicide.…”
Section: Study Population and Methodsmentioning
confidence: 99%